IMPROVE READING ABILITY UNDERSTANDING ME THROUGH A WHOLE LANGUAGE APPROACH ON OF CLASS IV SDN 12 CITY WEST (British Journal of Global Ecology and Sustainable Development, 2022)
The problem in this study is whether through the Whole Language Approach the Reading Comprehension of Grade IV Students at SDN 12 Kota Barat Increases? The research aims to improve reading comprehension skills through the Whole Language Approach in Grade IV students at SDN 12 Kota Barat . The type of research used in research is Classroom Action Research (CAR). The subjects of this study were 20 grade IV students at SDN 12 Kota Barat. Data Collection Techniques Using Observations, Tests and Documentation. Data analysis technique is done descriptively. Preliminary observations obtained data that out of a total of 20 students who were able only 6 people (30%) who were able to read comprehension and who were not able to read comprehension there were still 14 people (70%), research results in the implementation of Cycle I of 20 students there were 12 Students who can or (60%). While the Implementation of cycle II there were 17 people who were able or (85%) and who were unable there were 3 students or (15%). Based on the results of the research and discussion that has been done, it is concluded that through the Whole Language Approach the reading comprehension ability of Grade IV students at SDN 12 Kota Barat has increased.